The sustainable conflict of globalization And indicators of power rebalancingIn Islamic thought - Alwan, Hasan Abbas; Ismael, Maytham Elaibi (Journal of Economics and Administrative Sciences, 2021)
Our research was launched in the study of the sustainable conflict of globalization and the rebalancing of the great powers that have made life on the earth unstable and insecure over the past and present eras, the purpose of which is to pay attention to the waste and instability that human societies are exposed to in different proportions between abstract right and continuous deviation.The purpose of the study is to show the loss, waste and backwardness in managing and governing societies towards private interests, away from the standards of good institutional governance.The study’s design was based on two demands, the first on the nature and eternity of conflict and its true philosophy, and the second requirement on the reality of the crises resulting from the conflict and the mechanisms of intervention with arguments and the noble Qur’anic verses that represent the ability of God to intervene as is his capacity in creation.There are forces and standards that must be adhered to by human resources and work to conform to them in order to restore that deviation and correct the curvature, and this is what the research aimed at through the first requirement, the evidence and the consequences of God’s rule and his presence on earth, and this is what the second requirement demonstrated.And according to the hypothesis that indicates that the indicators and standards of governance in the Sharia of Islam are capable of restoring balance to those actions and personal judgments that give priority to the private interest over the public interest.The research is of great importance in terms of a philosophical analysis of what is actually happening in a modern and modern manner, with the necessity and importance of applying Islamic rulings and just Islamic legislation in the balance of power and achieving justice and the rule of law on the ground.The nature and type of research came as a study of the state of instability and the sustainability of the conflict between globalization and Islamic thought in terms of standards and style, and from the researcher's point of view, depending on the arguments and proofs that Islamic thought was based on.The research is considered as a study of reality and its eternal repercussions are continuing for our present time and as after. The researcher's viewpoint on the philosophy of standards that must be applied to reform good institutional governance is from its original tributaries